Strategi Komunikasi Krisis PT KAI dalam Menangani Kasus Tumbler Tuku: Analisis Menggunakan Situasional Crisis Communication Theory (SCCT) - Fitra Nur Suci; Suryani Musi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The case of lost tumblers that went viral at the end of November 2025 sparked public controversy after a KAI Commuter officer, Argi Budiansyah, uploaded a statement that he was fired due to the handling of reports of lost items by posting a thread on the Threads platform by the account @anitadewl which accused him of being irresponsible. The virality of the upload encouraged the formation of negative public attributions towards PT Kereta Api Indonesia (PT KAI), which was perceived to have taken unilateral decisions and acted unfairly towards its employees. This research aims to analyze PT KAI's crisis communication strategy in responding to this issue using the Situational Crisis Communication Theory (SCCT) framework. This research uses a qualitative approach with a case study method, with secondary data collection through analysis of uploads and comments on Threads social media, monitoring online media reporting, and literature review. The research results show that the crisis experienced by PT KAI is categorized as a preventable cluster, where the organization is perceived as fully responsible for the crisis due to alleged procedural and internal communication failures. The crisis response strategy implemented by PT KAI includes a deny strategy through clarification of the denial of unilateral dismissal, which is then followed by a rebuild strategy through facilitation of mediation between passengers and employees until a peace agreement is reached. Even though mediation measures have proven effective in reducing the escalation of negative conversations in the short term, these findings show that reputation restoration is not immediately achieved, because attributions of public responsibility have already settled through the dynamics of perceptions on social media.